Production of plasminogen activator inhibitor 1 by human adipose tissue: possible link between visceral fat accumulation and vascular disease - Alessi, M. C.; Peiretti, F.; Morange, P.; Henry, M.; Nalbone, G.; Juhan-Vague, I. (Diabetes (New York, N.Y.), 1997)
Production of plasminogen activator inhibitor 1 by human adipose tissue: possible link between visceral fat accumulation and vascular disease. M C Alessi , F Peiretti , P Morange , M Henry , G Nalbone and I Juhan-Vague CJF, Institut National de la Santé et de la Recherche Médicale (INSERM), Laboratoire d'Hématologie, Marseille, France. Abstract Plasminogen activator inhibitor type 1 (PAI-1) contributes to the pathogenesis of atherothrombosis. Its plasma level is strongly correlated with parameters that define the insulin resistance syndrome, in particular with BMI and visceral accumulation of body fat, suggesting that PAI-1 may be an adipose tissue-derived circulating peptide. The present study was designed to investigate PAI-1 expression by human adipose tissue and its different cellular fractions. Special interest has been paid to the amount of PAI-1 antigen produced by omental versus subcutaneous fat. PAI-1 protein detected by immunolocalization was present at the stromal and adipocyte levels. PAI-1 mRNA was detected in stromal vascular cells freshly isolated and under culture conditions. It was also detected in whole adipose tissue and adipocyte fraction under culture conditions. The mRNA signal from the adipocyte fraction was detected as early as 2 h of incubation. The increase in PAI-1 mRNA was followed by an increase in PAI-1 antigen in the conditioned medium that was suppressed by treatment with cycloheximide. Transforming growth factor-beta1 significantly increased PAI-1 antigen production by the adipocyte fraction, whereas tumor necrosis factor-alpha did not have any effect. Interestingly, after 5 h of incubation, omental tissue explants produced significantly more PAI-1 antigen than did subcutaneous tissue from the same individual, whereas similar production of leptin by the two territories was observed. These results strongly suggest that human adipose tissue, in particular visceral tissue, can be an important contributor to the elevated plasma PAI-1 levels observed in central obesity.